Proposal for the design of studies of intramammary antimicrobials to be conducted in Brazil for registration with the Ministry of Agriculture and Livestock - Kindlein, Giselle; Vasconcelos, Carla Gasparotto Chande; Lousana, Greyce Balthazar; Brandão, Humberto de Mello; Ávila, Isabela Maria Alves de; Zambelli, Luciana Sekito de Freitas; Ferrante, Marcos; Santos, Marcos Veiga dos; Gotti, Tatiana; Gomes, Viviani; Górniak, Silvana Lima (Brazilian Journal of Veterinary Research and Animal Science, 2024)
Before being made available to the Brazilian market, all veterinary medicines must be registered with the Ministry of Agriculture and Livestock after their efficacy, safety, and quality have been proven through clinical studies and scientific literature. Depending on the product class, the studies required by the regulatory authority must be carried out per Brazilian regulations and international reference guides. Some international organizations pursue the harmonization of these requirements, aiming at the mutual acceptance of studies conducted in different regions to facilitate international trade and reduce the use of animals in clinical research. Mastitis is one of the most prevalent and costly diseases in dairy cows, and it is associated with negative impacts on milk production and quality, cow welfare, and the profitability of the dairy industry. Normative Instruction No. 26/2009 determines a few rules for conducting studies for registering intramammary antimicrobials for cows with mastitis. However, the regulated sector and researchers report difficulties in following the recommendations of specific guidelines, which complement this regulation due to the peculiarities of Brazil’s production systems. This review article aims to provide subsidies and orientations that scientifically support the conduction and critical analysis of clinical studies proving the efficacy of intramammary products for treating clinical and subclinical mastitis in cows. Considering the need for scientific rigor in the studies, the recommendations available in international guidelines, and the need to adapt the protocols to the current situation of veterinary clinical research in Brazil, this document is intended to contribute to the internal harmonization of experimental protocols that support both the regulated sector and the regulatory authority.